2014
DOI: 10.1007/s00432-014-1750-z
|View full text |Cite
|
Sign up to set email alerts
|

Strong correlation between N-cadherin and CD133 in breast cancer: role of both markers in metastatic events

Abstract: N-cadherin and CD133 expressions are strongly correlated and N-cadherin appears as a potential metastases marker in a specific patient subpopulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 40 publications
2
33
1
Order By: Relevance
“…It has been reported that CD133 expression correlates significantly with TNBC subtype 30, 47. However, the biologic function of CD133 in TNBC has not yet been well established and its prognostic role still remains debated 24, 25. We did not find any evidence of CD133 in predicting aggressive properties and poor outcome in TNBC.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…It has been reported that CD133 expression correlates significantly with TNBC subtype 30, 47. However, the biologic function of CD133 in TNBC has not yet been well established and its prognostic role still remains debated 24, 25. We did not find any evidence of CD133 in predicting aggressive properties and poor outcome in TNBC.…”
Section: Discussioncontrasting
confidence: 73%
“…Studies in vitro have proven that CD133 is suitable for enriching BCSCs in TNBC 22, 23. For CD133+ phenotype, some studies documented poor prognosis in TNBC 24, while others did not 25. As the expression of these BCSC markers varied among different breast cancer subtypes, it appeared that each BCSC marker could have distinct clinical significance in different subgroups of breast cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Many cancer stem cell markers have been identified including CD133, CD44 + /CD22 − , and ALDH1 + in which CD133 is widely used as a cell surface marker in many cancer types including breast cancer . However, many groups commonly use ALDH1 in BCa, and this study confirms that high ALDH1 expression correlates with disease progression .…”
Section: Discussionsupporting
confidence: 72%
“…The high level of CDH-associated SC-TFs such as FOXM1, MCM2, SOX9, and SNAI1 were concurrent with the overexpression of CDH2, 4, 6, and 17 (Table 1), but mutually exclusive with the decrease of CDH1 (Supplementary Table  S2), strongly suggested that the enrichment of CSCs was more closely related to the high of CDH2, 4, 6, and 17, but not to the low of CDH1. Consistently, CDH2 has been identified as an indicator of EMT, and strongly correlated with CD133, one of the stem cell markers [11, 12, 83]. Moreover, CDH2 has a role in cell migration and metastasis over CDH1.…”
Section: Discussionmentioning
confidence: 79%